Why is sea buckthorn (Hippophae rhamnoides L.) so exceptional? A review - Ciesarová, Zuzana; Murkovic, Michael; Cejpek, Karel; Kreps, František; Tobolková, Blanka; Koplík, Richard; Belajová, Elena; Kukurová, Kristína; Daško, Ľubomír; Panovská, Zdenka; Revenco, Diomid; Burčová, Zuzana (Food research international (Ottawa, Ont.), 2020)
Sea buckthorn (Hippophae L.) is a valuable, multipurpose plant extensively grown in Asia, Europe and Canada. In order to use it in the best way for products of human nutrition, it is necessary to recognize its positive aspects and to eliminate the negative ones. The exceptional value of sea buckthorn can be seen in the presence of both lipophilic antioxidants (mainly carotenoids and tocopherols) and hydrophilic antioxidants (flavonoids, tannins, phenolic acids, ascorbic acid) in remarkably high quantities. Some of the main nutrients, especially lipids of advantageous fatty acid composition, contribute to nutritional benefits of sea buckthorn products for a consumer as well. This review article focuses, besides the above mentioned compounds and vitamins, also on other important components, such as sugars, sugar derivatives, fibre, organic acids, proteins, amino acids and mineral elements. The article also deals with the effects of sea buckthorn components on the course of non-enzymatic browning of food and in vivo glycation. In addition, sensory perception of sea buckthorn and its constituents from the consumers point of view is discussed.
Keywords: Amino acids; Sensory; Canada; Antioxidants; Hippophae rhamnoides; Europe; Asie; Fruit; Evropa; Kanada; ovoce; Carotenoids; Antiglycation; Hippophae; Tocopherols; Flavonoids; Ascorbic acid; Humans; Sea buckthorn; Asia; Fatty acids; lidé